Quality of life and socioeconomic indicators associated with survival of myeloid leukemias in Canada. Issue 1 (10th July 2020) - Cressman, Sonya; Hogge, Donna E.; Minden, Mark D.; Couban, Stephen; Karsan, Aly; Broady, Raewyn; McPherson, Emily; Halani, Khalif; Weng, Jing Yi; Peacock, Stuart J.
Abstract: Understanding how patient‐reported quality of life (QoL) and socioeconomic status (SES) relate to survival of acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) may improve prognostic information sharing. This study explores associations among QoL, SES, and survival through administration of the Euro‐QoL 5‐Dimension, 3‐level and Functional Assessment of Cancer Therapy‐Leukemia and financial impact questionnaires to 138 adult participants with newly diagnosed AML or MDS in a longitudinal, pan‐Canadian study. Cox regression and lasso variable selection models were used to explore associations among QoL, SES, and established predictors of survival. Secondary outcomes were changes in QoL, performance of the QoL instruments, and lost income. We found that higher QoL and SES were positively associated with survival. The Lasso model selected the visual analog scale of the EQ‐5D‐3L as the most important predictor among all other variables ( P  = .03; 92% selection). Patients with AML report improved QoL after treatment, despite higher mean out‐of‐pocket expenditures compared with MDS (up to $599 CDN/month for AML vs $239 for MDS; P  = .05), greater loss of productivity‐related income (reaching $1786/month for AML vs $709 for MDS; P  < .05), and greater caregiver effects (65% vs 35% caregiver productivity losses for AML vs MDS; P  < .05). Our results suggest that including patient‐reported QoL and socioeconomic indicators can improve the accuracy of survival models.